High‐throughput compositional mapping of triple‐cation tin–lead perovskites for high‐efficiency solar cells. Issue 4 (16th January 2023) - Gunasekaran, Rajendra Kumar; Jung, Jina; Yang, Sung Woong; Yun, Jungchul; Yun, Yeonghun; Vidyasagar, Devthade; Choi, Won Chang; Lee, Chang‐Lyoul; Noh, Jun Hong; Kim, Dong Hoe; Lee, Sangwook
Abstract: Mixed tin–lead perovskites suffer from structural instability and rapid tin oxidation; thus, the investigation of their optimal composition ranges is important to address these inherent weaknesses. The critical role of triple cations in mixed Sn–Pb iodides is studied by performing a wide range of compositional screenings over mechanochemically synthesized bulk and solution‐processed thin films. A ternary phase map of FA (Sn0.6 Pb0.4 )I3, MA(Sn0.6 Pb0.4 )I3, and Cs(Sn0.6 Pb0.4 )I3 is formed, and a promising composition window of (FA0.6− x MA0.4 Cs x )Sn0.6 Pb0.4 I3 (0 ≤  x  ≤ 0.1) is demonstrated through phase, photoluminescence, and stability evaluations. Solar cell performance and chemical stability across the targeted compositional space are investigated, and FA0.55 MA0.4 Cs0.05 Sn0.6 Pb0.4 I3 with strain‐relaxed lattices, reduced defect densities, and improved oxidation stability is demonstrated. The inverted perovskite solar cells with the optimal composition demonstrate a power conversion efficiency of over 22% with an open‐circuit voltage of 0.867 V, which corresponds to voltage loss of 0.363 V, promising for the development of narrow‐bandgap perovskite solar cells. Abstract : The optimal compositional space of tin–lead perovskites for narrow‐bandgap solar cells is revealed by the wide‐range compositional mapping of mechanochemically synthesized powders and solution‐processed films. Their targeted compositions as absorbers in inverted perovskite solar cells demonstrate over 22% efficiency with an open‐circuit voltage of 0.867 V, which is one of the highest among the 1.23 eV bandgap solar cells.